(untitled) (American International Journal of Education and Linguistics Research, 2019)
Evidence abounds on the fact that literacy and education are important for a developed State. Also, there are global records on the movement to a knowledge based economy rather than a resource based. Thus, globally efforts are being put in place to achieve a considerable percentage of literacy among citizens if not for all because a nation that refuses to place high premium on the education of her citizenry may be toying with her level of development. Nigeria is endowed with a rich culture and indigenous education but colonization disrupted the system she would have built upon to sustain her own philosophy. She is a signatory to policy documents on the attainment of Education for All (EFA). However, despite the institution of several policies on the promotion of literacy education from pre-independence till- date, Nigeria is still battling with a large population of illiterates especially, among its females; gender inequality and less development is evident in the society. This is a reflection of inadequate attention to lifelong learning opportunities for the citizenry. Policy formulation without adequate commitment towards development from all stakeholders also pervades the Nigerian society. This, question arise, will Universal Basic Education (UBE) thrive, especially within the context of the Sustainable Development Goals (SDGs) taking into cognizance, the past history and the present situation on the approach to enhancing lifelong and inclusive EFA in Nigeria? Can the Universal Basic Education enhance an equitable society which will create an enabling environment for an all-round oriented sustainable development with equal opportunities for all? More so, education is essential for societal development. This paper thus examine past education initiatives of the Nigerian government within the context of enhancing a lifelong well informed egalitarian society.